PENGARUH APLIKASI GEOGEBRA PADA MATERI BANGUN RUANG UNTUK KEMAMPUAN BERPIKIR KRITIS SISWA SMP NEGERI 1 GURAH - Ade Meyra Rahma; Darsono; Dian Devita Yohanie (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effectiveness of using the GeoGebra application in enhancing the critical thinking skills of junior high school students on the topic of three-dimensional shapes. The background of this research is based on the importance of critical thinking in mathematics learning and the need for interactive and contextual learning media. The method used is a pre-experimental design with a One Group Pretest-Posttest model. This study involved a sample of 35 students from class VIII G at SMP Negeri 1 Gurah, Kediri Regency. The research instrument consisted of tests that measured indicators of critical thinking skills, administered before and after learning using the GeoGebra application. The data analysis results showed that most students experienced an improvement in their critical thinking abilities. The pretest score was 60.71, which increased to 81.88 in the posttest. Based on the N-Gain classification, 85.75% of students were in the medium to high category. This improvement indicates that GeoGebra is effective in supporting the mathematics learning process, particularly in assisting visual understanding of concepts and increasing student engagement. Therefore, the use of the GeoGebra application can be an alternative learning media to improve students’ critical thinking skills. The researcher extends sincere gratitude to all parties involved, especially to SMP Negeri 1 Gurah, Kediri Regency.